Media Interaktif Pengenalan Angka Dengan Jari Tangan Menggunakan Metode PCA (Principal Component Analysis) - Haida Dafitri; Munjiat Setiani Asih; Rini Ida Astuti (Program Studi Sistem Informasi, 2019)
In computer science image processing, the scope of its development is very rapid, not only used on images, but also with the introduction of a video. Finger number recognition has now been developed for many applications and to help solve problems. The use of the hand as an identifier has many benefits, especially its practicality. The main problem is a camera that represents an image consisting of a relatively large size vector. There are many techniques to reduce the dimensions of the video or camera that will be processed, one of which will be discussed here is to implement interactive learning of numerical recognition with a finger, in the number recognition application with this finger will be detected the shape of the hand that can be captured by the camera which will identify a name (number). In designing this application, the author uses Visual Studio 2010 with the C sharp programming language (C#).Keywords: Hand recognition, interactive media, Principal Analysis Component